#178 Evaluation of RV forte capsules and TCCT (curcumin based formulation) tablets for its activity against anti-TB drug induced hepatotoxicity in wistar rats - Bodare, Snehal; Undale, Vaishali (Journal of Pharmaceutical Chemistry, 2022)
Anti-tubercular drugs (ATD) are the leading cause of drug-induced acute liver failure in India. The most effective first-line antitubercular drugs (ATD), Isoniazid (INH), and Rifampicin (RIF) have been used to treat tuberculosis (TB). The majority of potent ATDs, including INH, RIF, and Pyrazinamide, are hepatotoxic. When these medications are used together, the risk of hepatotoxicity increases, both of these medications are considered to be hepatotoxic due to their high potency against the tuberculous bacillus. The combination of both these drugs, however, resulted in the increase of hepatotoxicity both in adults and children. Anti-TB drugs are one of the commonest groups underlying idiosyncratic hepatotoxicity worldwide. The co-administration of hepatoprotective herb with the AntiTB drug may reduce the induced hepatotoxicity. The aim of the present study was to explore the hepatoprotective effect of RV forte capsules (resveratrol-based formulation) and TCCT (curcumin-based formulation) tablets for their hepatoprotective potential against INH induced hepatoxicity in Wistar rats at the dose of 100, 200, and 400 mg/kg dose. In this research work, RV forte TCCT tablets at 400 mg/kg dose showed a significant hepatoprotective effect against INH-induced hepatotoxicity, probably by reducing the oxidative stress as they exhibited a reduction in AST, ALT, and oxidative parameters, SOD, CAT, MDA. The liver histopathology also showed the amelioration of INH-induced hepatotoxicity.